Enhanced Pain Relief and Function Improvement in Children with Osgood-Schlatter Disease: Leukocyte-Rich Platelet-Rich Plasma (LR-PRP) as a Complementary Treatment to Standard Conservative Therapy - Guszczyn, Tomasz; Kulesza, Monika; Kicman, Aleksandra; Motyka, Joanna; Ławicki, Sławomir (Medical science monitor, 2023)
BACKGROUND Osgood-Schlatter disease (OSD) causes pain and loss of function of the knee in growing children. This study aimed to evaluate pain and function of the knee joint in 152 growing children with chronic OSD before and after treatment with LR-PRP when used with standard conservative treatment. MATERIAL AND METHODS Treatment efficacy was evaluated using the VAS, Tegner, Lyshom, and KOOS scales. Patient satisfaction, post-surgery athletic performance, and X-ray assessment were also used to determine the success of the procedure. RESULTS We found that 75% of the subjects were satisfied with the results of the treatment, and 72% of the subjects returned to full physical activity. The analysis showed a significant decrease in the median VAS score after treatment compared to the pre-treatment score (P<0.05), and an increase in the median scores of the Tegner, Lysholm, and KOOS scales compared to the pre-treatment score (P<0.05; P<0.05; P<0.05, respectively). The results showed that the shorter the duration of the disease, the better the treatment results were received. Return to activity and patient satisfaction were highest in the study group previously rehabilitated. CONCLUSIONS LR-PRP injection of the tibial tuberosity in patients with chronic OSD with open growth cartilage is an effective and uncomplicated method. We did not observe any adverse effects, which suggests the relatively high safety of the procedure. The use of PRP in the earlier phase of the disease and additional rehabilitation before treatment significantly increases the effectiveness of treatment.